Overexpression and characterization of medium-chain-length polyhydroxyalkanoate granule bound polymerases from Pseudomonas putida GPo1 - Ren Qun; de Roo Guy; Witholt Bernard; Zinn Manfred; Thöny-Meyer Linda (Microbial Cell Factories, 2009)
Abstract Background Polyhydroxyalkanoates (PHA) are synthesized by many bacteria in the cytoplasm as storage compounds for energy and carbon. The key enzymes for PHA biosynthesis are PHA polymerases, which catalyze the covalent linkage of 3-hydroxyacyl coenzymeA thioesters by transesterification with concomitant release of CoA. Pseudomonas putida GPo1 and many other Pseudomonas species contain two different class II polymerases, encoded by phaC1 and phaC2. Although numerous studies have been carried out on PHA polymerases and they are well characterized at the molecular level, the biochemical properties of the class II polymerases have not been studied in detail. Previously we and other groups purified the polymerases, however, the activities of the purified enzymes were several magnitude lower than the granule-bound enzymes. It is problematic to study the intrinsic properties of these enzymes with such low activities, although they are pure. Results PHA polymerase 1 (PhaC1) and PHA polymerase 2 (PhaC2) from P. putida GPo1 were overexpressed in the PHA-negative host P. putida GPp104 and purified from isolated PHA granules. Only minor activity (two to three orders of magnitude lower than that of the granule bound proteins) could be recovered when the enzymes were purified to homogeneity. Therefore, kinetic properties and substrate ranges were determined for the granule bound polymerases. The polymerases differed significantly with respect to their association with PHA granules, enzyme kinetics and substrate specificity. PhaC2 appeared to bind PHA granules more tightly than PhaC1. When R-3-hydroxyoctanoic acid was used as substrate, the granule-bound PhaC1 exhibited a Km of 125 (± 35) μM and a Vmax of 40.8 (± 6.2) U/mg PhaC1, while a Km of 37 (± 10) μM and a Vmax of 2.7 (± 0.7) U/mg PhaC2 could be derived for the granule-bound PhaC2. Granule-bound PhaC1 showed a strong preference for medium chain length (mcl-) 3-hydroxyacly-CoAs, with highest affinity towards 3-hydroxydecanoyl-CoA (40 U/mg PhaC1). Granule-bound PhaC2 demonstrated a far broader specificity ranging from short chain length up to long chain length substrates. Activity increased with increasing chain length with a maximum activity for 3-hydroxyacyl-CoAs containing 12 or more C-atoms. Conclusion The kinetic properties and substrate ranges were determined for both granule bound polymerases. Evidence was provided for the first time that two PHA polymerases exhibited significant differences in granule release and in vitro activity profiles, suggesting that there are substantial functional differences between granule bound PhaC1 and PhaC2.